Peran Komunikasi Interpersonal Dalam Meningkatkan Kepuasan Dan Loyalitas Karyawan: Studi Literatur - Muhammad Ilham; Lisa Andesta; Novan Darlind Pratama; Muhammad Azka; Susriyanti . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Interpersonal communication is an important factor in building effective working relationships within organizations. This paper aims to examine the role of interpersonal communication in enhancing job satisfaction and employee loyalty based on a literature study. The method employed is a literature review by analyzing various scientific journals and academic sources relevant to interpersonal communication, job satisfaction, and employee loyalty. The findings indicate that effective interpersonal communication—such as openness, clarity of messages, and two-way feedback between supervisors and employees—has a positive effect on job satisfaction. Increased job satisfaction subsequently encourages the development of employee loyalty and organizational commitment. These findings emphasize that interpersonal communication not only functions as a means of information exchange but also serves as an important strategy in human resource management to create a harmonious and productive work environment